The crystal structure of mouse VDAC1 at 2.3 Å resolution reveals mechanistic insights into metabolite gating - Ujwal, Rachna (National Academy of Sciences, 2008)
The voltage-dependent anion channel (VDAC) constitutes the major pathway for the entry and exit of metabolites across the outer membrane of the mitochondria and can serve as a scaffold for molecules that modulate the organelle. We report the crystal structure of a β-barrel eukaryotic membrane protein, the murine VDAC1 (mVDAC1) at 2.3 Å resolution, revealing a high-resolution image of its architecture formed by 19 β-strands. Unlike the recent NMR structure of human VDAC1, the position of the voltage-sensing N-terminal segment is clearly resolved. The α-helix of the N-terminal segment is oriented against the interior wall, causing a partial narrowing at the center of the pore. This segment is ideally positioned to regulate the conductance of ions and metabolites passing through the VDAC pore.